2019
DOI: 10.1158/1078-0432.ccr-18-3389
|View full text |Cite
|
Sign up to set email alerts
|

Plasma HER2 (ERBB2) Copy Number Predicts Response to HER2-targeted Therapy in Metastatic Colorectal Cancer

Abstract: Purpose: ERBB2 (HER2) amplification is an emerging biomarker in colon cancer, conferring sensitivity to combination anti-HER2 therapy. Measurement of HER2 copy number is typically performed using surgical specimens, but cell-free circulating tumor DNA (ctDNA) analysis may be a noninvasive alternative. We determined the sensitivity of plasma copy number (pCN) for detecting ERBB2 amplifications and whether pCN correlated with tissue-detected copy number. We also assessed response to HER2-targeted therapy based o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 27 publications
3
86
1
Order By: Relevance
“…ERBB2 copy number amplification was also evident in CRC liquid biopsies in patient plasma. Siravegna et al reported that when 3 or more copies of ERBB2 were found in circulation, this led to reduced progression free survival in 46 patients [51]. Even though we did not observe ERBB2 overexpression at the transcript level, upstream analysis shows it as a common denominator for several of our up-regulated transcripts, which suggest an activated state of ERBB2 in CRC.…”
Section: Discussioncontrasting
confidence: 60%
“…ERBB2 copy number amplification was also evident in CRC liquid biopsies in patient plasma. Siravegna et al reported that when 3 or more copies of ERBB2 were found in circulation, this led to reduced progression free survival in 46 patients [51]. Even though we did not observe ERBB2 overexpression at the transcript level, upstream analysis shows it as a common denominator for several of our up-regulated transcripts, which suggest an activated state of ERBB2 in CRC.…”
Section: Discussioncontrasting
confidence: 60%
“…Immunohistochemistry and fluorescence in situ hybridization analysis are considered the standard assays to detect HER2 amplifications. HER2 amplification by ctDNA is dependent on both disease tumor burden and degree of HER2 amplification within the tumor . In the current study, 2 HER2 amplifications were detected on G360 testing, both of which were 1+ amplifications and were discordant with our F1 assay.…”
Section: Discussionsupporting
confidence: 53%
“…26,27 Currently, the clinical utility of ctDNA is only approved in metastatic non-small-cell lung cancer (NSCLC) by FDA as a companion diagnostic, 28,29 while studies on many other cancers have also shown good prospects. [30][31][32][33][34][35][36] The fact that even little variability in process and analysis will result in completely different results restrains the further clinical utility of ctDNA. 37 In order to solve these problems, some projects, such as the European CANCER-ID, European Liquid Biopsy Academy (ELBA) and European Liquid Biopsy Society (ELBS) networks or the US-based BloodPAC, have been initiated.…”
Section: Discussionmentioning
confidence: 99%